The atlas of religion - O'Brien, Joanne, 1959-; Palmer, Martin; Barrett, David B.; O'Brien, Joanne, 1959- (Berkeley : University of California Press, 2007)
Maps the current nature, extent, and influence of each of the major religions and shows, country by country, how religions are spread through broadcasting, missionary work, schooling, and banking; how they relate to government, laws, and world hunger; and the role they play in wars. It traces the emergence of new religious movements, the survival of traditional beliefs, and the presence of atheism and agnosticism. The Atlas of Religion also locates the origin, the heartland, and the sacred places of each of the major religions and provides essential background with a valuable table showing the fundamental beliefs of Buddhism, Christianity, Hinduism, Islam, Judaism, Sikhism, and Taoism.--From publisher description.
pt. 1. Beginnings : Popular religions, Arrivals, Roots and branches -- pt. 2. Beliefs, Christianity, Islam, Hinduism, Buddhism, Judaism, Sikhism, Traditional beliefs, Catholicism, New religious movements, New departures, Non-believers -- pt. 3. Structures, State attitudes to religion, Christian finance, Religious education, Christian missionaries, The word, Christian broadcasting, Aid and development, Islamic law -- pt. 4. Conflicts and tensions, Faultlines, Emerging from persecution -- pt. 5. Contemporary challenges, Shared world, Equal rites, Environmental protection, Ethical investment, The future -- pt. 6. The heartlands, Origins, Holy natural, Fundamentals of the faiths -- pt. 7. Social context.
Rev. ed. of: The state of religion atlas.
Includes bibliographical references and index.
Keywords: Religions -- Maps; Religions -- History -- Maps; Atlases